The Effect of Times Game Tournement on Ball Playing Skills of Sports Students of Medan State University - Mahmuddin; Waskita, Ghozi Indra; Pane, Bessy Sitorus; Manik, Syahputra; Argubisilwan; Yudhistira, Dewangga (Indonesian Journal of Sport Management, 2025)
Background: Learning in soccer courses for sports students at Medan State University is needed, one of which is the times games tournament (TGT) method. However, the TGT method in the scope of college students has not received special attention. Purpose: The purpose of this study was to test the TGT method to optimize ball playing skills (dribbling, receiving, shooting) in sports students at Medan State University. Methods: The research method was experimental with one group pretest-posttest control group; participants were 20 students who were divided into two groups of TGT and control by applying matched ordinal pairing. The instrument is the skill of playing the ball. Data collection techniques include observational and field tests. Data analysis techniques with nonparametric tests, Wilcoxon and Man-Whitney, assisted with SPSS version 25. Results: found pretest-posttest sig value of TGT and control groups (0.000<0.05). TGT and control group posttest comparison was found (0.000<0.05). Conclusion: times games tournament method is better than the control group in soccer playing skills. Implications and Recommendations: There is a need for improvement in future research with an individualized approach and a longer period of time to be more optimal.